The role of hearing capability test as a screening test for the possibility of hearing disorder in children with speech delay - Fatmawaty Fatmawaty; Hartono Gunardi; Ronny Suwento; Abdul Latief; Rulina Suradi; Irawan Mangunatmadja (Indonesian Pediatric Society, 2006)
Background Hearing disorder may cause speech delay so thatevery child with speech delay should undergo hearing test. Thegold standard for audiometric test is otoacustic emission (OAE)and brainstem evoked response audiometry (BERA). They havehigh sensitivity and specificity, but the availability is limited andexpensive. Hence, both tests are not available at the primary healthcare centers. In 1997, the Department of Health, Republic of Indo-nesia, established a simple subjective test instrument, i.e. the hear-ing capability test (HCT).Objective To asses the accuracy of HCT compared to the goldstandard hearing tests (OAE and/or BERA).Methods This study was a cross sectional study on 89 childrenaged less than 5 years who had speech delay and came to theGrowth and Development Outpatient Clinic or the General Outpa-tient Clinic, Pediatric Neurology Clinic of the Department of ChildHealth, Cipto Mangunkusumo (CM) Hospital; and Center for EarCare and Communicative Disorders (CECCD), Department of ENT,CM Hospital, during March to August 2005.Results HCT sensitivity and specificity were 92.9% and 27.7%,respectively. Positive predictive value (PPV), negative predictivevalue (NPV), positive likelihood ratio (PLR), and negative likehoodratio (NLR) were 84%, 50%, 1.9, and 0.7, respectively.Conclusion The sensitivity and specificity of HCT as a screeningtest of hearing disorder in children with speech delay were 93%and 28%, respectively. Based on this result, HCT should only beused as screening test and not as a diagnostic test